Financial security and economic safety as the basis for sustainable development of the region - Dziamulych, Mykola; Antoniuk, Nataliia; Tretyak, Viktoriia; Rudenko, Mykola; Solomnikov, Ivan; Kytaichuk, Tetiana; Khomiuk, Nataliia; Shmatkovska, Tetiana (My University, 2023)
The article studies importance of financial provision and economic security as main components of sustainable development of a region. It considers interconnection between proper functioning of the financial system and achievement of stability of the regional economy. The role of effective resource management, investment activity and financial support in achieving sustainable development is analysed. The necessity of prevention of financial risks and introduction of effective mechanisms of ensuring socioeconomic security is proved. The key problems affecting the sustainable development of the region, in particular, resource availability, competitiveness and innovation potential, are identified. An approach to ensuring a balance between financial indicators and social needs to achieve economic stability and sustainable growth of the region is proposed
Keywords: financial support; economic security; sustainable development; region; investment; resource availability; competitiveness; socioeconomic security